Improvement of sperm function, chromatin damage, and oxidative damage by N-Acetyl cysteine in varicocelized rats model - Tavalaee, Marziyeh; Dattilo, Maurizio; Mohammadi, Parisa; Nasr-Esfahani, Mohammad Hossein (Archives of Men's Health, 2020)
Introduction: N-Acetylcysteine (NAC), an acetylated form of the amino acid cysteine and precursor of reduced glutathione, plays important roles in a multitude of cellular processes, such as oxidative damage and detoxification of many electrophiles. Considering the pathophysiology of oxidative stress induced infertility in varicocele, we aimed to investigate the effect of NAC on semen analysis parameters (light microscopy), chromatin structure (aniline blue and acridine orange staining), and lipid peroxidation (BODIPY probe) in varicocelized rats. Methods: In this experimental study, varicocelizing surgery was carried out on 30 Wistar rats. Ten of them were sacrificed after two months (one round spermatogenesis), together with control rats (n=10) and sham operated rats (n=10), to verify the varicocele model. Out of the remaining twenty varicocelized rats, ten received NAC while ten were treated with water (control group) for two months. Results: All the investigational parameters (sperm parameters, chromatin integrity, and lipid peroxidation) severely worsened 2 and 4 months after surgical varicocele. The administration of NAC for two months significantly improved all the investigational parameters as compared to control rats at four months (p<0.05). Conclusion: The supplementation of varicocelized rats with NAC was effective in antagonizing the damage as well as in preserving testicular structure and spermatogenetic function. These effects are likely to occur also in clinical varicocele.